Pengaruh Corporate Governance Terhadap Dividen (Studi pada Bank yang Terdaftar di BEI Tahun 2011-2014) - . Yefni (Jurnal Akuntansi dan Keuangan, 2016)
The test aimed to examine the effect of corporate governance towards dividend using three controlling variables are profitability (ROA), BOPO, and bank growth. In order to measure banking corporate governance practice in Indonesia, the measurement criteria of good corporate governance developed by Mahdan (2010) is used. The samples used in this research are banks listed in Indonesian Stock Exchange period 2011-2014 were selected using purposive sampling with criteria of banks registered on the Indonesian Stock Exchange during the research period, which pay the dividend as well as publish the annual statement during the period of research. Based on these criteria, there are 36 research samples obtained. To test the hypothesis proposed in this study, researcher used multiple regression analysis. The result shows that corporate governance does not generate significant effect towards dividend. The results also indicate that the outcome theory applies in Indonesia in connection with the implementation of corporate governance. In addition, the result of this study indicate that three controlling variables were tested, only the profitability variable (ROA) that significantly influenced the dividend.